Computers helping people with special needs. 16th International Conference, ICCHP 2018, Linz, Austria, July 11-13, 2018, Proceedings /: 16th International Conference, ICCHP 2018, Linz, Austria, July 11-13, 2018, Proceedings. Part I : (2018) - Unknown
No abstract available